The role of cognitive reserve in the relationship between metabolic syndrome and cognitive functioning. Issue 5 (3rd September 2021) - Strong, Jessica; Fonda, Jennifer R.; Grande, Laura; Milberg, William; McGlinchey, Regina; Leritz, Elizabeth
ABSTRACT: Metabolic syndrome (MetS) is a cluster of vascular risk factors that can impact cognition. Cognitive reserve (CR), specifically early operators of reserve (e.g., education), have not been explored in the relationship between MetS and cognition. Adults 45–90 years old (n = 149) underwent neuropsychological testing and evaluation for MetS. Exploratory and confirmatory factor analyses defined neuropsychological domains and created a CR score based on early operators of CR. Regression analyses examined the association among MetS, CR,  and neuropsychological performance. CFA revealed two neuropsychological factors: Episodic Memory and Executive Functioning. Controlling for age and physical ability, MetS and CR were significant predictors of the Factors. With CR in the model, MetS became a non-significant predictor of Executive Functioning; CR and physical ability were the most significant predictors. CR and MetS significantly predicted Episodic Memory . The results are discussed in the context of neuroprotective factors and cognitive aging.